Independence of elderly persons living in the rural areas in performing basic and complex everyday activities - Dziechciaż, Małgorzata; Płaszewska-Żywko, Lucyna; Guty, Edyta (Polish Journal of Public Health, 2010)
Aim. The aim of this thesis was to evaluate functioning of elderly people living in rural areas. Material and methods. The research method was based on a survey with the direct interview technique. It included six research tools: a self-made questionnaire, Hodkinson’s Abbreviated Mental Test Score, the Katz ADL Scale, the Lawton IADL Scale, the Tinetti Assessment Tool. The study was carried out among 102 people (56 females, 46 males), 60-86 years old (average 73.18) in the Podkarpacie Province. The investigated group had good intellectual performace. Results. The majority of the researched group (90.2%) were independent in activities of daily living (ADL). The majority of the investigated (66.7%) had a lot of problems with instrumental activities of daily living (IADL). No significant differences in activities of daily living and instrumental activities of daily living were discovered between men and women. However, it was found out that when people get older, their functioning worsens in ADL and IADL (p